2018
DOI: 10.1029/2018gc007765
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations in Vent Chemistry at the Lucky Strike Hydrothermal Field, Mid‐Atlantic Ridge (37°N): Updates for Subseafloor Flow Geometry From the Newly Discovered Capelinhos Vent

Abstract: This study aims at characterizing the subseafloor architecture of the Lucky Strike hydrothermal field (LSHF) based on an extensive chemical database of the various vents. Our analysis is motivated by the discovery in 2013 of a new active high‐temperature site, named Capelinhos, approximately 1.5 km east of the LSHF. Capelinhos fluids display particular chemical features with chloride and metal (Fe and Mn) concentrations 2 times lower and 4 times higher, respectively, compared to other vent sites. Trace element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 80 publications
(155 reference statements)
6
52
0
Order By: Relevance
“…Indeed, the LSHF hosts about ~30 active hydrothermal vents distributed over its 1 km 2 surface area. At this location, Chavagnac et al (2018a) and Leleu (2017) showed that high-temperature hydrothermal fluids contain DSr concentrations that are either lower or higher than seawater depending on the vent. In particular, the vents located on the western and north-eastern sides of the LSHF contain 94-179 µmol/L of DSr and all the south-eastern vents display 74-81 µmol/L of DSr (light blue boxes in Figure 2A, and Supplementary Table S2; Von Damm et al, 1998;Charlou et al, 2000;Pester et al, 2012;Chavagnac et al, 2018a).…”
Section: Hydrothermal Input Of Strontium In the Water Columnmentioning
confidence: 89%
See 2 more Smart Citations
“…Indeed, the LSHF hosts about ~30 active hydrothermal vents distributed over its 1 km 2 surface area. At this location, Chavagnac et al (2018a) and Leleu (2017) showed that high-temperature hydrothermal fluids contain DSr concentrations that are either lower or higher than seawater depending on the vent. In particular, the vents located on the western and north-eastern sides of the LSHF contain 94-179 µmol/L of DSr and all the south-eastern vents display 74-81 µmol/L of DSr (light blue boxes in Figure 2A, and Supplementary Table S2; Von Damm et al, 1998;Charlou et al, 2000;Pester et al, 2012;Chavagnac et al, 2018a).…”
Section: Hydrothermal Input Of Strontium In the Water Columnmentioning
confidence: 89%
“…A better understanding of lithium (Li) and strontium (Sr) oceanic biogeochemical cycles is needed nowadays based on two main issues: 1) their oceanic cycles are still under debate, and 2) they are two economically relevant elements. Li and Sr are widely used to estimate several geochemical processes notably at the water/ rock interface (Huh et al, 1998;Brunskill et al, 2003;Davis et al, 2003) such as continental weathering (Pistiner and Henderson, 2003;Vance et al, 2009;Millot et al, 2010) or hydrothermal alteration of oceanic crust (Barker et al, 2008;Araoka et al, 2016;Chavagnac et al, 2018a). It is generally admitted that dissolved riverine inputs and hydrothermal inputs are the two main sources of Li and Sr to the ocean (Albarède et al, 1981;Palmer and Edmond, 1989;Allègre et al, 2010;Tomascak et al, 2016;von Strandmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. azoricus, B. seepensis, A. lutzi, P. valvatoides and L. atlanticus), which have been previously described as indicator species of cold microhabitats on the Eiffel Tower edifice situated ~ 50 m from Montségur (Sarrazin et al, 2015b). The high similarity between the fauna from the two edifices may be related to their belonging to the same chemistry domain (Chavagnac et al 2018). Among the 43 macrofaunal species identified on Montségur, approximately 74% exhibit a low frequency of abundance (<1%).…”
Section: Pre-disturbed Communities and Natural Variabilitymentioning
confidence: 99%
“…Subaerial volcanoes, back-arc systems and mid-ocean ridges have been widely investigated in terms of hydrothermal vents distribution and circulation pattern by bathymetric and backscatter, magnetics, electro-magnetics, gravity and seismic methods 1215 . High-resolution multibeam bathymetry constrains spatially hydrothermal activity 6,16 , while vent chemistry helps to determine the source of hydrothermal fluids as well as fluid crustal residence time related to rock permeability 17 . However, the lack of direct information, such as drilling, makes numerical modelling an important tool in understanding fluid/rock interactions and hydrothermal circulation within an active tectonic setting 18,19 .…”
Section: Introductionmentioning
confidence: 99%